Short stories for Japanese learners : learn Japanese with an authentic and fun short story collection for beginners. Volume 1 - Nishino, Yumi; Niimi, Nankichi, 1913-1943; Ogawa, Mimei, 1882-1961; Oki, Kazuhiko; Easthope, Alessandro; Nishikawa, Shino (Monee, IL : Japanese Language Park, 2023)
"Suitable for new learners who have learned Hiragana and Katakana and are able to read short sentences in simple grammar."
CSE
Hye Trade International
In Japanese with translation in English.
Keywords: Japanese language -- Readers; Japanese language -- Study and teaching -- Foreign speakers; Japanese language -- Textbooks for foreign speakers; Short stories, Japanese